Entrepreneurial Innovation: A Resilience Strategy - Edeh, F.O; Joseph, O.A; Alamina, U.P; Osueke, N.C; Onyemaechi, U (Department of Entrepreneurship, FMSC, USJ, 2020)
The paper explored the effect of entrepreneurial innovation on firm resilience in selected Nigerian hospitality firms using a cross-sectional survey. Twenty hotels that are registered with the Enugu State Ministry of Culture and Tourism were surveyed with a simple random sampling technique. The demographic profiles were analyzed using frequency distribution and linear regression was employed to analyze the formulated hypotheses. The study found that entrepreneurial innovation dimensions have a positive significant effect on situation awareness and adaptability. It was concluded that entrepreneurial innovation measured in terms of service innovation and marketing innovation enhances the resilience capacity of hospitality firms through situation awareness and adaptability. The implication of this study is that entrepreneurs in both hospitality and service-oriented sectors should embrace innovation in service delivery to their esteemed customers to enhance their resilience capacity.
Keywords: Entrepreneurial innovation, resilience, service innovation, marketing innovation, adaptability, situation awareness.